1990
DOI: 10.1112/jlms/s2-42.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Subgroups of Infinite Symmetric Groups

Abstract: LEMMA 2.1. / / r /^Q and \Y 1 n F 2 | = minflFJ, |F 2 |} then U F 2 ) = Since the combinatorial argument given in [8] for the case where T x and F 2 are countably infinite needs only trivial modification to prove this we omit details. LEMMA 2.2. If all moieties ofQ are full for the subgroup G of S then G = S.This is [19, Note 3(iii) of §4] and we will not rehearse the proof here. LEMMA 2.3. Let H be a subgroup of S and let EpEg be subsets ofQ. that are full for H. If |Z X n I 2 | = K and Z x U S 2 = ft then H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
110
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 13 publications
0
110
0
Order By: Relevance
“…For a semigroup S, if A ⊆ S then we call the minimum cardinality of a set B such that A ∪ B = S, the relative rank of S modulo A. Alternatively, we may refer to this cardinality as the relative rank of A in S; which we denote by rank(S : A). This subject has been studied in the context of groups in [2] and [14]. In these papers, so called large subgroups of the symmetric group S X , over an infinite set X, were considered.…”
Section: Introductionmentioning
confidence: 99%
“…For a semigroup S, if A ⊆ S then we call the minimum cardinality of a set B such that A ∪ B = S, the relative rank of S modulo A. Alternatively, we may refer to this cardinality as the relative rank of A in S; which we denote by rank(S : A). This subject has been studied in the context of groups in [2] and [14]. In these papers, so called large subgroups of the symmetric group S X , over an infinite set X, were considered.…”
Section: Introductionmentioning
confidence: 99%
“…A deep theorem of Macpherson and Neumann [16] states that if the symmetric group Sym(κ) consisting of all permutations of a cardinal κ can be written as a union of an increasing chain G i : i < λ of proper subgroups G i , then λ > κ. Throughout this paper the minimal λ with this property will be denoted by cf(Sym(κ)).…”
Section: Introductionmentioning
confidence: 99%
“…So there is a finite set B such that Aut(R), B = Sym(R). (This fact follows from Theorem 1.1 of [43]. Galvin [30] showed that we can take B to consist of a single element.…”
Section: Theorem 210mentioning
confidence: 70%